The Effect of Foliar Feeding With University Fertilizer on The Growth and Yield of Green Onion Plants Allium Cepa, The Local White Variety, Planted in Southern Iraq: Pengaruh Pemberian Pupuk Daun Dengan Pupuk Universitas Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah Allium Cepa Varietas Lokal Putih yang Ditanam di Irak Selatan - Al Khazraji, Haidar A.K.; Athfua, Qasim Jasim; Abdlulla, Abdulla A. (Universitas Muhammadiyah Sidoarjo, 2024)
The experiment was conducted during the winter agricultural season 2023-2024 at the Agricultural Research Station of the Faculty of Agriculture, University of Basra, in the Kerma Ali area, with the aim of studying the impact of different concentrations of liquid sky (university fertilizer) on the growth and yield of green onions of the white local variety and four different sprays (0, 3, 6, 9) ml-1, so it was carried out according to the design of the complete random sectors with three repetitions and the arithmetic averages of the transactions were compared according to the test of the lowest moral difference LSD and it has a significance level of 0.05. The results showed that the concentration of spraying exceeded 6 ml liters-1 Significantly in the height of the plant, the number of tubular leaves, the soft weight of the vegetative total, the diameter and weight of the onion, the total onion yield and the total green yield. The values were as follows ( 75.3 cm, 13.3 leaves, 141.6g, 4.2 cm, 64.5 g, 3.783 tons, -1 0.307 tons, -1) respectively. Highlights: Evaluate liquid sky fertilizer effects on green onion growth, yield. Tested 0, 3, 6, 9 ml/L on green onions, LSD 0.05. 6 ml/L improved plant height, leaves, weight, yield significantly. Keywords: green onion, university fertilizer, leaf spray, growth, yield